Spectrophotometric determination of plasma and red blood cell cholinesterase activity of 53 fruit farm workers pre- and post-exposed chlorpyrifos for one fruit crop - Anamai Thetkathuek (2018)
We sought to investigate the early biological effects of chlorpyrifos among 53 Thai fruit farm workers by measuring the plasma cholinesterase (PChE) and red blood cell cholinesterase (AChE) activities, a biomarker of organophosphate (OPs) pesticide during one fruit crop. The ChE activity (Vm/K m) was spectrophotometrically analyzed before and after exposing to chlorpyrifos. The Vm/Km values of both non-spraying and spraying seasons are found as normal distribution pattern. The median PChE and AChE activities among farm workers in the non-spraying season were 2.3×10-3s-1 and 7.26×10-5s -1, respectively. The median PChE and AChE activities of the farm workers in the spraying season were 2.02×10-3s-1 and 5.95×10-5s-1, respectively. The mean V m/Km values of PChE shifted left (t-test, p=0.013), indicating a decrease in PChE activity in the farm workers exposed to chlorpyrifos. However, the Vm/Km values of AChE in nonspraying season and in the spraying season were not different (t-test, p=0.246). We propose that PChE activity can be used as a biomarker for monitoring early toxicity induced by chlorpyrifos insecticide. © 2005 Pharmaceutical Society of Japan.